Analisis Yuridis Tindak Pidana Perjudian Bola Guling (Studi Kasus Berdasarkan Berita Acara Pemeriksaan Saksi Dari Laporan Polisi No. Pol.: Lp/A/K/02/X/2025/Sat Reskrim/Polres Belu) - Finsensius Samara; Hilarianti G.S Nahak; Suzanthyka M.C Ballo; Serafina J. Taneo; Maria P.F Asten; Kasumi Matsushita; Alexandro G.E.M Maya (LPPM Institut Pendidikan Nusantara Global, 2026)
Gambling is one of the most frequently encountered crimes in society, both through print and electronic media, and in everyday activities. There are numerous motives behind gambling crimes. Gambling crimes are usually motivated by the perpetrator's daily life circumstances, such as economic circumstances or a low income that makes it impossible to cover daily living expenses, as well as a low level of education. One fact that cannot be ignored is that, in some cases, gambling crimes are often